Optic Nerve Pilocytic Astrocytoma in a Pediatric Patient: A Case Report - Pramantara, I Made Stepanus Biondi; Niryana, I Wayan; Sista Satyarsa, Agung Bagus Sista; Golden, Nyoman; Mahadewa, Tjokorda Gede Bagus; Maliawan, Sri; Suarjaya, I Putu Pramana (Jurnal Neuroanestesi Indonesia, 2024)
Pilocytic astrocytoma is a type of low-grade glioma that can develop in any part of the central nervous system. It primarily affects individuals in the pediatric and young adult age groups. Optic nerve pilocytic astrocytoma is an uncommon, gradually developing type of brain tumor known as a glioma. It is categorized as a grade I tumor by the World Health Organization (WHO). We aim to report rare optic nerve pilocytic astrocytomas and discuss their clinical findings and interconnection with the current literature. A 7-year-old male patient exhibited left-sided eye proptosis and complete loss of vision. A magnetic resonance imaging (MRI) performed before surgery showed the presence of a tumor in the left eye socket. The mass has a spherical shape and smooth boundaries, resulting in the compression of the left optic tract from behind. The left optic tract appears darker on T1-weighted images and brighter on T2-weighted images. On contrast administration, there is heterogenous contrast enhancement. A total resection of the mass was performed. Histopathology results show pilocytic astrocytoma (WHO Grade I). Optic nerve pilocytic astrocytoma is a tumor that can affect the optic nerve pathway. Early diagnosis and multidisciplinary team management are required. Treatment must be individualized, and the options include chemotherapy, radiotherapy, and surgical intervention. Surgery is only recommended in cases of painful or disfiguring proptosis and exposure keratopathy in eyes with severe vision impairment.